How interethnic marriages affect the educational attainment of children: evidence from a natural experiment - Jan C. van Ours; Justus Veenman (Institute for the Study of Labor (IZA), 2008)
The allocation of Moluccan immigrants across towns and villages at arrival in the Netherlands and the subsequent formation of interethnic marriages resemble a natural experiment. The exogenous variation in marriage formation allows us to estimate the causal effect of interethnic marriages on the educational attainment of children from such marriages. We find that children from Moluccan fathers and native mothers have a higher educational attainment than children from ethnic homogeneous Moluccan couples or children from a Moluccan mother and a native father.
Keywords: I21; 300; Interethnic marriages; educational attainment; Ethnische Beziehungen; Ehe; Kinder; Bildungsniveau; Niederlande